Profile of Student Career Aspirations and Their Implications for Career Guidance Services at SMAN 1 Koto XI Tarusan - Handayani, Sri; Putri, Besti Nora Dwi; Suryadi, Suryadi (Holistic Science, 2022)
This research is motivated by the existence of students who are still confused in deciding their career aspirations towards work or college, the existence of students where they will continue their careers after graduating from high school education. This study aims to determine the profile of the career aspirations of students and their implications for career guidance services at SMAN 1 Koto XI Tarusan in terms of: 1) Aspects of Intention. 2) Attitude Aspect. 3) Behavioral Aspect This type of research is descriptive quantitative. The population of this study was class XII students, totaling 132 students. The sampling technique was carried out using a purposive random sampling technique, namely as many as 57 students who became the research sample. The analysis used in this research is the percentage. The results of this study on the profile of the career aspirations of students and their implications for career guidance services at SMAN 1 Koto XI Tarusan show: 1) Career aspirations seen from the aspect of intention are in many categories. 2) Career aspirations seen from the attitude aspect are in many categories. 3) Career aspirations seen from the behavioral aspect are in many categories. This research is recommended for students to consult with BK teachers about career planning that will be taken.